Roles Of Transforming Growth Factor-Beta, Insulin-Like Growth Factors And Proteases In Human Breast Cancer - Wong, Shew Fung (2002)
Transforming growth factor-beta (TGF) is present in breast cysts, normal and cancerous breast tissue. It plays an important role in oestrogen metabolism. However, TGF is present predominantly in latent form and the mechanisms by which latent TGF is activated physiologically remain largely an enigma. The aims of this study were: 1) to investigate the effects of TGF B' IGF-I and IGF-II on cell growth, E1STS and E2DH activities in the hormone-dependent MCF-7 and honnone-independent MDA-MB-231 human breast cancer cell lines. 2) to investigate the effect of Cathepsin D and PSA on TGFl and TGF2 mRNA expression, and their protein levels in both of the cell lines. 3) to study the effect of Cathepsin D and PSA on Type 1 and Type 2 E2DH mRNA expression, EJ and E2 levels in both cell lines.